2000
DOI: 10.1046/j.1365-2443.2000.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Central role for Cdc45 in establishing an initiation complex of DNA replication in Xenopus egg extracts

Abstract: Background: In eukaryotes, chromosomal DNA is licensed to be replicated through the sequential loading of the origin recognition complex, Cdc6 and mini-chromosome maintenance protein complex (MCM) onto chromatin. However, how the replication machinery is assembled onto the licensed chromatin during initiation of replication is poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
132
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(144 citation statements)
references
References 42 publications
10
132
1
1
Order By: Relevance
“…Similarly, in Xenopus cell-free extracts, association of Pol ⑀ with chromatin during DNA replication can occur in the absence of Pol ␣ or replication protein A (RPA) (Mimura et al, 2000). Based on these findings, Mimura et al 2000 proposed that Pol ⑀ might associate with chromatin before synthesis of RNA primers by Pol ␣. We are currently testing whether the binding of Pol ␣ or RPA to replication origins occurs before, or is dependent on, the prior loading of Dpb2 or Pol ⑀.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in Xenopus cell-free extracts, association of Pol ⑀ with chromatin during DNA replication can occur in the absence of Pol ␣ or replication protein A (RPA) (Mimura et al, 2000). Based on these findings, Mimura et al 2000 proposed that Pol ⑀ might associate with chromatin before synthesis of RNA primers by Pol ␣. We are currently testing whether the binding of Pol ␣ or RPA to replication origins occurs before, or is dependent on, the prior loading of Dpb2 or Pol ⑀.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, association of Pol ␣ with ARS-associated chromatin requires Dpb11, a protein that both genetically and physically interacts with Pol ⑀ (Masumoto et al, 2000). Similarly, in Xenopus cell-free extracts, association of Pol ⑀ with chromatin during DNA replication can occur in the absence of Pol ␣ or replication protein A (RPA) (Mimura et al, 2000). Based on these findings, Mimura et al 2000 proposed that Pol ⑀ might associate with chromatin before synthesis of RNA primers by Pol ␣.…”
mentioning
confidence: 99%
“…3) indicate that cohesin is efficiently acetylated even under conditions in which PCNA is not recruited to chromatin, for example in the presence of the Cdk inhibitor p27. Previous work has shown that Cdk activity is required for recruitment of Cdc45, polymerase ␣, and PCNA to chromatin (36,37). This observation calls into question whether interaction of XEco2 with PCNA is important in vertebrate systems as it is in yeast.…”
Section: Xeco2mentioning
confidence: 99%
“…S-CDK targets two additional proteins, Sld2 and Sld3, causing them to associate with Dpb11 and eventually resulting in the recruitment of the GINS proteins as well as DNA Pol 1 (Tanaka et al 2007;Zegerman and Diffley 2007;Muramatsu et al 2010). The subsequent activation of DNA unwinding is required for the recruitment of the lagging-strand DNA polymerases (DNA Pol a-primase and DNA Pol d (Mimura et al 2000;Heller et al 2011).…”
Section: A Model For Helicase Loadingmentioning
confidence: 99%